Comparison of the efficiency of two adsorbents (activated carbon and beech wood powder copper-modified) in removing sulfide ions (S-2) from Kraft pulping black liquor - M. Mollaei (Regional Information Center for Science and Technology (RICeST), 2021)
Sulfide ions (S-2) derived from Na2S remaining in kraft black liqueur are the source of H2S gas production in recovery cycle in the Kraft pulping. In this study, we tried to prevent the production of H2S by removing the mentioned ions from black liquor using synthesized adsorbents (Cu-PAC and Cu-BWP100). The adsorbents were produced by immersing activated carbon (PAC) powder and 100 mesh beech powder (BWP100) in 0.1 M solution of CuCl2. The adsorbent properties were measured before and after copper ion loading by FTIR, BET and SEM-FEI analyses. Finally, the performance of these adsorbents in the removal of S-2 from black liquor with three levels of sulfide (22%, 20 and 18) was investigated. The results of FTIR, BET and SEM-FEI analysis showed that Cu+ 2 was located on the surfaces of raw organic material without any change in their structure. Experimental data for the Cu-PAC adsorbent showed that it was more agreement with the Freundlich equation and follow to the pseudo-second-order kinetic model, whereas for Cu-BWP100 adsorbent was more consistent with the Langmuir equation and adherence to the pseudo-first-order kinetic model. The Cu-PAC adsorbent had the ability to remove 79.93% and Cu-BWP100 at 60.03% of S-2 from black liquor. The Cu-PAC, with its higher specific surface area, has a higher ability to remove S-2 from the black liquor than the Cu-BWP100. In general, the mentioned adsorbents will have a high ability to reduce H2S production by eliminating S-2.